Proof Mining: A Systematic Way of Analysing Proofs in Mathematics - Kohlenbach, Ulrich; Oliva, Paulo B. (BRICS Report Series, 2002)
We call proof mining the process of logically analyzing proofs in mathematics with the aim of obtaining new information. In this survey paper we discuss, by means of examples from mathematics, some of the main techniques used in proof mining. We show that those techniques not only apply to proofs based on classical logic, but also to proofs which involve non-effective principles such as the attainment of the infimum of f in C[0,1] and the convergence for bounded monotone sequences of reals. We also report on recent case studies in approximation theory and fixed point theory where new results were obtained.